Virome analysis for identification of novel mammalian viruses in bat species from Chinese provinces - Wu, Zhiqiang; Ren, Xianwen; Yang, Li; Hu, Yongfeng; Yang, Jian; He, Guimei; Zhang, Junpeng; Dong, Jie; Sun, Lilian; Du, Jiang; Liu, Liguo; Xue, Ying; et al. (Journal of virology, 2012)
Bats are natural hosts for a large variety of zoonotic viruses. This study aimed to describe the range of bat viromes, including viruses from mammals, insects, fungi, plants, and phages, in 11 insectivorous bat species (216 bats in total) common in six provinces of China. To analyze viromes, we used sequence-independent PCR amplification and next-generation sequencing technology (Solexa Genome Analyzer II; Illumina). The viromes were identified by sequence similarity comparisons to known viruses. The mammalian viruses included those of the Adenoviridae, Herpesviridae, Papillomaviridae, Retroviridae, Circoviridae, Rhabdoviridae, Astroviridae, Flaviridae, Coronaviridae, Picornaviridae, and Parvovirinae; insect viruses included those of the Baculoviridae, Iflaviridae, Dicistroviridae, Tetraviridae, and Densovirinae; fungal viruses included those of the Chrysoviridae, Hypoviridae, Partitiviridae, and Totiviridae; and phages included those of the Caudovirales, Inoviridae, and Microviridae and unclassified phages. In addition to the viruses and phages associated with the insects, plants, and bacterial flora related to the diet and habitation of bats, we identified the complete or partial genome sequences of 13 novel mammalian viruses. These included herpesviruses, papillomaviruses, a circovirus, a bocavirus, picornaviruses, a pestivirus, and a foamy virus. Pairwise alignments and phylogenetic analyses indicated that these novel viruses showed little genetic similarity with previously reported viruses. This study also revealed a high prevalence and diversity of bat astroviruses and coronaviruses in some provinces. These findings have expanded our understanding of the viromes of bats in China and hinted at the presence of a large variety of unknown mammalian viruses in many common bat species of mainland China.